Foreign direct investment and military expenditure in the face of terrorism: evidence from Sub-Saharan Africa - Niaz Ahmed, Mohd Naseem bn; Kabiru, Alhaji (Opast Group, 2024)
This study examines the relationship between military expenditure and foreign direct investment (FDI) amid terrorism. The study used Mean Group, Pooled Mean Group, Dynamic Fixed Effect, and Panel Quantile estimations techniques on 23 terrorized countries in Sub-Sharan Africa from 1999 to 2019. The outcome of the estimate discovered that military expenditure in the absence of terrorism negates FDI flow. But, amid terrorism, military expenditure has a significant positive impact on FDI inflow. Also, the results show that the effect varies at different quantiles. The results are robust using death from terrorism attacks to measure terrorism on a different model. The study suggests that countries should desist from high military spending in the absence of terrorism to facilitate FDI flow. Countries in mid-life terrorism should enhance military spending and augment military strategy with other options to boost investors' confidence in the economy's high influx of FDI.